Recommendations on Collecting and Storing Samples for Genetic Studies in Hearing and Tinnitus Research. Issue 2 (March 2019) - Szczepek, Agnieszka J.; Frejo, Lidia; Vona, Barbara; Trpchevska, Natalia; Cederroth, Christopher R.; Caria, Helena; Lopez-Escamez, Jose A.
Abstract : Objectives: Research on the genetic basis of tinnitus is still in its first steps. A group of scientists dedicated to tinnitus genetics within European Tinnitus Network (TINNET) network recognize that further progress requires multicenter collaborative efforts for defining contributing genes. The purpose of the present work is to provide instructions regarding collection, processing, storage, and shipment of samples intended for genetic studies in auditory research. Design: One part of the recommendations has a general character; another part is of particular importance for auditory healthcare practitioners such as otolaryngology physicians, audiologists, and general practitioners. Results: We provide a set of instructions and various options for obtaining samples. We give advice regarding sample processing, storage, and shipment and define the minimal and essential clinical information that should accompany the samples collected for genetic processing. Conclusions: These recommendations offer a basis to standardize and optimize collaborations between geneticists and healthcare practitioners specialized in tinnitus and hearing disorders.